Penggunaan Google Classroom pada Pembelajaran Daring dalam Meningkatkan Hasil Belajar Matematika - Wiwin, Wiwin (LPPM Universitas Bina Bangsa, 2022)
The purpose of this study was to determine the use of Google Classroom in Online Learning in Improving Mathematics Learning Outcomes. The research method used in this research is descriptive qualitative research, with reference to problem solving strategies. The reason for using this qualitative descriptive research is because the author wants to improve and improve the quality of learning. In addition, this research is an effort to improve the writer's performance. The research was conducted on the XII IPA grade students of SMAN 2 Singaparna, Tasikmalaya Regency. The research subjects were students of class XII IPA SMAN 2 Singaparna, Tasikmalaya Regency with a total of 36 students. Based on this article, the following conclusions can be drawn: 1) Learning mathematics using Google Classroom during the covid-19 pandemic in class XII IPA at SMAN 2 Singaparna is beneficial for students so that students can still carry out learning even with limitations. 2) The advantages of using Google Classroom, teachers and students become accustomed to using online learning. Barriers to the use of Google Classroom, teachers and students cannot meet face to face in learning. If the facilities are inadequate, it can hinder the implementation of online learning